PENERAPAN STRATEGI PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUAL, INTELEKTUAL) UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA SISWA SMP KELAS IX - Sari, Siti Wulan; Syahril, Syahril; Ma‟aruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to determine the improvement of understanding physics concept of SMP class IX with the application of SAVI (somatic, auditory, visual, intellectual) learning strategy. This study is a pre-experimental One-Group Pretest-Posttest. The subject of this research are the 25 students of class IX SMP Negeri 3 Kampar Kiri. The design of this research is pre-experiment with the data collection instrument used was a concept comprehension test, in the question is in the form of multiple choice and grounded consisting of 15 items about static electricity. Students are given the first concept comprehension test (Pretest) first to see the level of understanding of the initial concept of students, after that is given treatment or treatment by applying SAVI learning strategy, then the students are given the final concept of comprehension test (poststtest) at the end of the learning process. The data were analyzed descriptively by using N-Gain. Increased understanding of student concepts is shown by the N-Gain value of each indicator. Based on the data obtained, the N-Gain value is categorized as high for translation and interpretation indicator, while for extrapolation indicator is in medium category. Based on the result, it can be concluded that the implementation of SAVI learning strategy can improve the physics concept conception of class IX SMP Negeri 3 Kampar Kiri.Key words: Learning Strategy, SAVI, Concept Understanding, Static Electricity